Pengaruh Brand Image dan Kualitas Produk Terhadap Loyalitas Pelanggan dengan Kepuasan Sebagai Variabel Intervening pada Pelanggan Roti Kacang Mpok Atik - Dio Wiranda; Raka Gymnastiar Sasmita; Mangasi Sinurat; Cia Cai Cen (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
This study aims to determine the Influence of Brand Image and Product Quality on Customer Loyalty with Satisfaction as an Intervening Variable on Mpok Atik Peanut Bread Customers. The research method used is a quantitative method using Smart PLS version 3.0. The questionnaire was distributed to 97 respondents. The data analysis method used in the study is the measurement model (outer model), namely the validity test, reliability test, then the structural model (inner model) including: coefficient of determination/r-square (r2) and hypothesis testing with t-statistics and indirect effect tests. The results of Smart PLS 3.0 in this study are that Brand Image has an effect on Customer Satisfaction of Mpok Atik Peanut Bread Customers, Product Quality does not have an effect on Customer Satisfaction of Mpok Atik Peanut Bread Customers, Brand Image has an effect on Customer Loyalty of Mpok Atik Peanut Bread Customers, Product Quality does not have an effect on Customer Loyalty of Mpok Atik Peanut Bread Customers, Customer Satisfaction does not have an effect on Customer Loyalty of Mpok Atik Peanut Bread Customers, Brand Image does not have an effect on Customer Loyalty with Customer Satisfaction as an Intervening Variable on Mpok Atik Peanut Bread Customers, Product Quality does not have an effect on Customer Loyalty with Customer Satisfaction as an Intervening Variable on Mpok Atik Peanut Bread Customers.